Direct measurement of Young's modulus, fracture strength and fracture toughness of nanocrystalline diamond foil by means of tensile testing - Kachold, Franziska; Lodes, Matthias; Rosiwal, Stefan; Singer, Robert (Acta Materialia, 2013)
A tensile testing method to directly determine the elastic as well as the fracture properties of self-supporting nanocrystalline diamond foil (NCDF) is introduced. NCDF is the strongest ceramic foil material known, offering a bending strength of more than 4 GPa [1]. The previously presented bending test reflects the influence of the surface morphology on the mechanical properties well, but is limited to a small near-surface volume. Hence only a small number of different flaws in the material can be detected. To investigate the bulk properties of this novel material a tensile testing method, where the stress is evenly distributed over the whole cross-section of the sample, was developed and validated. The interpretation of the tensile strength by the statistical Weibull approach resulted in values of ∼535 MPa and 470 MPa for NCDF grown on silicon and copper templates, respectively. The combination of tensile testing with digital image correlation allows for the direct determination of Young's modulus. As compared to methods using resonance frequencies this technique does not have limitations regarding the thickness of the specimen. Young's modulus was found to yield 624 ± 88 GPa for NCDF synthesized on polished silicon and 536 ± 65 MPa for NCDF from an etched silicon template. Furthermore, by stressing the double-edge-notched specimen in this set-up, the fracture toughness was determined to be 3.5±0.7MPam. © 2013 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Chemical vapor deposition; Digital image correlation; Mechanical properties; Nanocrystalline diamond foil; Tensile testing

Mechanical Properties of Carbon Fiber-Reinforced Aluminum Manufactured by High-Pressure Die Casting - Kachold, Franziska; Singer, Robert (Journal of Materials Engineering and Performance, 2016)
Carbon fiber reinforced aluminum was produced by a specially adapted high-pressure die casting process. The MMC has a fiber volume fraction of 27%. Complete infiltration was achieved by preheating the bidirectional, PAN-based carbon fiber body with IR-emitters to temperatures of around 750 °C. The degradation of the fibers, due to attack of atmospheric oxygen at temperatures above 600 °C, was limited by heating them in argon-rich atmosphere. Additionally, the optimization of heating time and temperature prevented fiber degradation. Only the strength of the outer fibers is reduced by 40% at the most. The fibers in core of fiber body are nearly undamaged. In spite of successful manufacturing, the tensile strength of the MMC is below strength of the matrix material. Also unidirectional MMCs with a fiber volume fraction of 8% produced under the same conditions, lack of the reinforcing effect. Two main reasons for the unsatisfactory mechanical properties were identified: First, the fiber-free matrix, which covers the reinforced core, prevents effective load transfer from the matrix to the fibers. And second, the residual stresses in the fiber-free zones are as high as 100 MPa. This causes premature failure in the matrix. From this, it follows that the local reinforcement of an actual part is limited. The stress distribution caused by residual stresses and by loading needs to be known. In this way, the reinforcing phase can be placed and aligned accordingly. Otherwise delamination and premature failure might occur.
Keywords: carbon fibers; composites; metallic matrix; modeling and simulation; residual stress; tensile testing

Mechanical properties of micro- and nanocrystalline diamond foils - Lodes, Matthias; Kachold, Franziska; Rosiwal, Stefan (Philosophical Transactions of the Royal Society A-Mathematical Physical and Engineering Sciences, 2015)
Diamond coating of suitable template materials and subsequent delamination allows for the manufacturing of free-standing diamond foil. The evolution of the microstructure can be influenced by secondary nucleation via control of process conditions in the hot-filament chemical vapour deposition process. Bending tests show extraordinarily high strength (more than 8 GPa), especially for diamond foils with nanocrystalline structure. A detailed fractographic analysis is conducted in order to correlate measured strength values with crackinitiating defects. The size of the failure causing flaw can vary from tens of micrometres to tens of nanometres, depending on the diamond foil microstructure as well as the loading conditions.
Keywords: Fractography; Hot-filament chemical vapour deposition; Mechanical testing by tensile test and ball-on-three-balls bending test; Self-supporting nanocrystalline diamond foil

Mechanical Properties, Surface Structure, and Morphology of Carbon Fibers Pre-heated for Liquid Aluminum Infiltration - Kachold, Franziska; Kozera, Rafal; Singer, Robert; Boczkowska, Anna (Journal of Materials Engineering and Performance, 2016)
To efficiently produce carbon fiber-reinforced aluminum on a large scale, we developed a special high-pressure die casting process. Pre-heating of the fibers is crucial for successful infiltration. In this paper, the influence of heating carried out in industrial conditions on the mechanical properties of the fibers was investigated. Therefore, polyacrylonitrile-based high-tensile carbon fiber textiles were heated by infrared emitters in an argon-rich atmosphere to temperatures between 450 and 1400Â Â°C. Single fiber tensile tests revealed a decrease in tensile strength and strain at fracture. Young’s modulus was not affected. Scanning electron microscopy identified cavities on the fiber surface as the reason for the decrease in mechanical properties. They were caused by the attack of atmospheric oxygen. The atomic structure of the fibers did not change at any temperature, as x-ray diffraction confirmed. Based on these data, the pre-heating for the casting process can be optimized.
Keywords: advanced characterization; aluminum; casting and solidification; composites; heat treatment; metallic matrix

Zusammenhang von Prozess, Mikrostruktur, Eigenspannungen und Eigenschaften bei Aluminiumverbundwerkstoffen - Kachold, Franziska (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2016)